PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN LABUHAN HAJI BARAT - Rahman, Ziahul (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Every organization must have a leader with diverse characteristics and styles for guiding employees and organizations. The style and attitude of a leader is the method by which he or she can direct other individuals or a group to achieve specific objectives. This study aims to determine the presence and absence of the influence of the leadership style of the work environment and communication on the performance of employees of the West Labuhan Haji Sub-district office. This research is a descriptive qualitative research, namely by using a method through distributing questionnaires to sub-district office employees as respondents. Data collection in this study was carried out through deepening, interviews, questionnaires, and documentation studies, the sempel used in this study was all employees of the West Labuhan Haji Sub-district Office. Based on the results of the study, it can be concluded that the influence of leadership style and work environment as well as communication has a significant effect on the level of performance achievement of employees of the West Labuhan Haji Sub-district Office.